2008
DOI: 10.2298/sos0803319k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold swaging and heat treatment on properties of the P/M 91W-6Ni-3Co heavy alloy

Abstract: This paper describes the effects of rotary swaging and heat treatment under different conditions on mechanical properties and microstructure of the P/M 91W-6Ni-3Co alloy. The investigation was performed on cold rotary swaging rods with 10, 20 and 25% reduction in area, heat treated at 11300C for 90min under different cooling conditions and strain-aged at temperatures from 300 to 8000C for 60, 180 and 360min. Tensile and toughness testing of rotary swaging rods showed that increase in the reduction resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…On the other hand, ductility and impact resistance were deeply decreased by about 75% and 53% respectively, by also, the application of 50% area reduction by swaging. It was shown by M. Nikačević et al [8,9] that, During rotary swaging, strength intensively increases, while ductility and toughness were found to be quite reduced compared to the init ial sintered condition. A high gradient of hardness in the rods cross section can be noticed as well.…”
Section: Effect On the Physical And Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, ductility and impact resistance were deeply decreased by about 75% and 53% respectively, by also, the application of 50% area reduction by swaging. It was shown by M. Nikačević et al [8,9] that, During rotary swaging, strength intensively increases, while ductility and toughness were found to be quite reduced compared to the init ial sintered condition. A high gradient of hardness in the rods cross section can be noticed as well.…”
Section: Effect On the Physical And Mechanical Propertiesmentioning
confidence: 99%
“…Moreover, a clearly visible grain deformation can be recognized particularly at the structures subjected to heavy percentages of deformat ion under the swaging process. B. Katavić [8,9] reported that, there are no significant changes in the W phase grain size or in the volume fract ion of W and matrix phases as an effect of plastic deformat ion after rotary swaging while the mean distance between W-grains was found to be reduced. While the longitudinal cross -section Microstructure of the adopted heavy tungsten alloy specimens obtained under different values of area reductions by rotary swaging was shown in Fig.5.…”
Section: Effect On the Physical And Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten and its alloys because of their unique characteristics have wide application in many sectors of the industrial production [1][2][3]. One of the topical applications of tungsten materials is the thermonuclear energy, where tungsten can be used for protection against plasma of parts of the first wall and the diverter [4,5], because of its operational strength to 20 times higher than the resistance of iron, copper, beryllium and 10 times-molybdenum.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, many preparation technologies of tungsten heavy alloys have been reported, such as spark plasma sintering and microwave sintering [4][5][6], cold rolling [7][8][9], highpressure torsion [10][11][12], rotary swaging [13][14][15][16][17][18][19][20][21][22][23], hot extrusion [24][25][26], hydrostatic extrusion [27][28][29][30]. But, many publications up to the present have shown that hydrostatic extrusion is one of the most effective processes for deformation strengthening technique for the consolidation of powder materials, especially difficult-to-deform materials, such as WHAs including W-Ni-Fe [27][28][29][30], and W-Cu series alloys [31][32].…”
Section: Introductionmentioning
confidence: 99%